Facet-controlled bifunctional WO3 photocathodes for high-performance photo-assisted Li–O2 batteries. Issue 2 (10th January 2023) - Wang, Meng; Chen, Jie; Tian, Zhangliu; Dai, Wenrui; Cui, Baihua; Cui, Xinhang; Wang, Dong; Xiao, Yukun; Lian, Xu; Jiang, Chonglai; Yang, Haotian; Wang, Yihe; et al.
Abstract : Facet-engineered monoclinic WO3 was investigated to explore the effects on the photo-assisted LOB kinetics and discharge mechanism. This work can pave the way for rational photocathode design in metal–O2 batteries. Abstract : Photocatalytic materials have been recently incorporated into Li–O2 batteries to mitigate the challenge of high overpotential. However, the structure–activity relationship between photocatalytic materials and charge–discharge mechanisms in photo-assisted Li–O2 batteries has rarely been experimentally revealed. Herein, we take facet-engineered WO3 as a prototype to investigate the formation processes of discharge products and photocatalytic reaction activities. A combination of theoretical and experimental results demonstrates that a controllable transition of the generated Li2 O2 from the solution growth route to the surface growth route with faster redox kinetics can be realized by increasing the exposed (002)/(020) facet ratio of WO3 photocathodes. Furthermore, the (002) facet is revealed to possess higher oxidation ability for Li2 O2 decomposition, thus resulting in an ultralow polarization overpotential of 0.07 V over the (002) facet dominant WO3 photocathode. Importantly, the continuous growth of the Li2 O2 film up to ∼130 nm through the surface growth mode is observed on the photocathode. In-depth studies show that a Z-type heterojunction tends to be formed between the WO3 and formed Li2 O2, facilitating continuous growth of the Li2 O2 film under illumination. As a result, a high discharge capacity of up to 10500 mA h g −1 is also achieved over the (002) facet dominated WO3 photocathode. These new discoveries break through the limitation of premature battery death caused by the surface growth route and enable high capacities and sustained photo-assisted discharge.